John Updike - American Writers 79 : University of Minnesota Pamphlets on American Writers - Samuels, Charles Thomas, 1936-1974 (Book collections on Project MUSE., 1969)
John Updike - American Writers 79 was first published in 1969. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions.